Antioxidant Activity Of Platelet Rich Plasma Wistar Rats With Dpph And Abts Test - Wienaldi; I Nyoman Ehrich Lister; Bungaran Sihombing (CV. Inara, 2022)
Free radicals and reactive oxygen species (ROS) are the cause of diseases such as cancer, diabetes, cardiovascular and inflammatory. The presence of an increase in the number of free radicals and excess ROS production in the body can cause an imbalance of the immune system. Therefore, additional antioxidants are needed from outside the body. During this time there are several antioxidant synthesis drugs such as (Butyl Hydroxy Anisole) BHA and (Butyl Hydroxyl Toluene) BHT. But in its use, this drug causes side effects. Therefore, it is necessary to source antioxidants that have no side effects if consumed. PRP is a product produced from fresh whole blood that contains components of Red blood cells, White blood cells, Platelets, and Plasma. Plasma contains organic and inorganic molecules and ions wherein abundant conditions serve to transport other substances. To determine the ability of PRP as an antioxidant, fractionation, and bioactivity tests for free radical capture of 1,1-diphenyl-2-picrilhydrazil (DPPH) and color decay tests at 2,2'-azino-bis-[3-ethylbenzotiazolin sulfonate] (ABTS) in vivo.. Based on the results of this study, PRP has antioxidant activity that increases along with the decrease in THE concentration of PRP with an antioxidant activity value of 10.57% with the DPPH test and 5.85% with the ABTS test at the lowest concentration (6.25 μg / mL). IC50 averages 190.29 μg/mL with DPPH test and 126.60 μg/mL with the ABTS test. The results of this study are an indication that PRP can be used as a treatment therapy related to the anti-oxidant activity